Bacteria laden street food (Chatpati) and their multiple antibiotic resistance index - Khan, Farhana Islam; Saha, Mihir Lal (Bangladesh Journal of Botany, 2018)
The bacteria associated with street food Chatpati and their multi-drug resistance pattern were investigated. The highest bacterial load of solid part of Chatpati was recorded on NA as 1.07×105 - 9.7×105 cfu/g followed by 1.55×104 - 4.05×105 cfu/g on EMB. In case of liquid part (Spicy tamarind) maximum load was 3.1×102 - 6.4×104 cfu/ml on SS agar. The bacterial isolates were provisionally identified as Escherichia coli, Klebsiella sp., Enterobactor sp., Micrococcus variens, Staphylococcus aureus, Streptococcus faecalis and Salmonella paratyphi A. Multiple antibiotic resistance index (MRI) was found between 14.28 and 71.43%. Escherichia coli, Klebsiella sp., Enterobacter sp. and Salmonella paratyphi A showed the highest MRI percentage. Bacterial high loads and the presence of many enteric bacteria indicated significant food contamination. The presence of multi-drug resistant bacteria is very much alarming for the city dwellers habituated with the popular snacks like Chatpati.